2020
DOI: 10.1002/jbmr.4508
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-3 Enhances Osteogenic Differentiation of Precursor Cells From Patients With Diffuse Idiopathic Skeletal Hyperostosis via Wnt/β-Catenin Signaling

Abstract: Diffuse idiopathic skeletal hyperostosis (DISH) is a noninflammatory skeletal disease characterized by the progressive ectopic ossification and calcification of ligaments and enthuses. However, specific pathogenesis remains unknown. Bone marrow mesenchymal stem cells (BMSCs) are a major source of osteoblasts and play vital roles in bone metabolism and ectopic osteogenesis. However, it is unclear whether BMSCs are involved in ectopic calcification and ossification in DISH. The current study aimed to explore the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 42 publications
0
5
0
1
Order By: Relevance
“…Moreover, treatment with HMGB1 remarkably increased the expression of RAGE in human BMSCs during osteogenic differentiation [ 27 ]. In addition, β -catenin interacts with TCF-4 in the nucleus to activate the transcription of osteogenic genes and has emerged as a critical regulator of the osteogenic differentiation of stem cells [ 30 32 ]. Increased RAGE could promote osteogenic differentiation of vascular smooth muscle cells and calcification via modulating downstream β -catenin signaling [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, treatment with HMGB1 remarkably increased the expression of RAGE in human BMSCs during osteogenic differentiation [ 27 ]. In addition, β -catenin interacts with TCF-4 in the nucleus to activate the transcription of osteogenic genes and has emerged as a critical regulator of the osteogenic differentiation of stem cells [ 30 32 ]. Increased RAGE could promote osteogenic differentiation of vascular smooth muscle cells and calcification via modulating downstream β -catenin signaling [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, intracellular β -catenin signaling has emerged as a critical regulator of the osteogenic differentiation of stem cells [ 30 , 31 ]. In the nucleus, β -catenin is known to interact with transcription factor-4 (TCF-4) and activates the transcription of osteogenic genes [ 32 ]. Wang et al [ 33 ] showed that HMGB1 exerted a pro-osteogenic effect on human bone marrow-derived MSCs (BMSCs) via activating the β -catenin signaling.…”
Section: Introductionmentioning
confidence: 99%
“…Mesenchymal stem cells (MSCs) are upstream progenitor cells with the ability to proliferate and differentiate [8]. Bone marrow mesenchymal stem cells (BMSCs) are important targets for studying bone-related diseases such as osteoporosis (OP), osteoarthritis (OA), and hyperostosis [9][10][11][12]. Integrins expression is dynamically regulated during BMSCs osteogenic differentiation.…”
Section: Integrins Regulate Migration Adhesion and Differentiation Of...mentioning
confidence: 99%
“…У пошуках механізмів дії вітаміну D на остеокласти дослідники звернули увагу на галектин-3, нещодавно відкритий регулятор кісткового метаболізму, який бере участь у проліферації, диференціації та апоптозі різних типів клітин [63]. Фактор транскрипції галектин-3 у ядрі остеокластів розташований поряд з VDR.…”
Section: вплив вітаміну D на остеокластиunclassified